The influence of water content in rice husk bio-oil on the rheological properties of coal bio-oil slurries. (15th December 2019) - Yi, Shuping; Hao, Lifang; Li, Songgeng; Song, Wenli
Abstract: Bio-oil from biomass pyrolysis is a mixture of water and organic compounds, which can be used to prepare coal bio-oil slurry (CBS) by blending with coal. The water content in bio-oil has significant effect on the properties of CBS. 57 CBS samples with Shenmu coal concentration of 31–40 wt% and water content in rice husk bio-oil from 27.40 to 48.71 wt% were prepared. The rheology, thixotropy, characteristic viscosity, maximum solid concentration and static stability of the samples were tested. The results showed that the samples could be divided into two groups based on its rheological behavior: strong pseudoplastic and weak pseudoplastic CBS. During storage, all strong pseudoplastic samples were unstable but most of weak pseudoplastic samples were stable. With the increase of water content in bio-oil, CBS behavior changed from weak pseudoplastic to strong pseudoplastic and the transition occurred in the water content of about 45 wt%. Strong pseudoplastic CBS usually showed larger yield stress and thixotropic loop area compared with weak pseudoplastic ones. For all CBS samples, there was a water content in bio-oil where the characteristic viscosity of CBS was the minimum, and its value decreased with the increase in coal concentration. Highlights: CBS samples can be divided into strong pseudoplastic and weak pseudoplastic CBS. Strong pseudoplastic CBS were unstable but most weak pseudoplastic CBS were stable. Strong pseudoplastic CBS usually had large yield stress and obvious thixotropy. There is a water content in bio-oil where characteristic viscosity was the minimum.